Mob1, hippo pathway member, is critical for toxoplasma gondii replication - Tavares, Alexandra (2017)
Toxoplasma gondii is an obligate intracellular parasite of great veterinary and medical importance. It is able to evade the immune system of the host by converting from rapidly proliferating tachyzoites to latent bradyzoite cysts and this parasite number control is a key to the success of the infection. Pathways controlling cell division/proliferation like the Hippo pathway are likely candidates for regulating parasite replication. Human Mob1 participates in this pathway and our recent data suggests it is an excellent candidate for the control of parasite replication/number. Our research group has identified a single mob1 gene in T. gondii. A phylogenetic analysis of this gene showed it to be similar to other Apicomplexa but distant from protozoan parasites like the Trypanosomatida. We confirmed that this gene is expressed and our data show that its expression dramatically decreases (94%) during the parasite replication inside the host cell. We have constructed a transgenic parasite strain that overexpresses Mob1 and these parasites show a significant delay in the replication process. Using an in-house polyclonal antibody against this protein we observed a very clear polarized localization of the protein in the parasite posterior pole, where the basal complex, a structure involved in cytokinesis in T. gondii, is localized. To better understand the role of Toxoplasma Mob1 we have created, by using the by CRISPR/Cas9 approach, a strain where Mob1 loss of function can be induced. Our preliminary results, by immunofluorescence microscopy, show that after induction Toxoplasma parasites in parasitophorous vacuoles (PV) lose their intrinsic polarity and their normal rosette organization. Indeed, inside of the PV, it is difficult to identify the individual dividing parasites that seem to have originated a mass of abnormal cells where multiple nuclei are present. This result suggests that Toxoplasma cells have abnormal division and/or fail the cytokinesis. Altogether, the data support that Mob1 is involved in the control of T. gondii replication and is a promising candidate to target therapeutic agents against Toxoplasma parasites proliferation.